ANALISIS PERAN KOMODITAS PERTANIAN TERHADAP EKONOMI DESA LEFOKISU DI KECAMATAN ALOR BARAT LAUT - Inang Naila Mustapa; Jesenia Loriance Alelang; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study aims to analyze the role of agricultural commodities in the economy of the Lefokisu Village community, Alor Barat Laut District. The agricultural commodities that are the main source of income for the community consist of corn, tamarind, and cashew seeds, which are processed and sold to meet family economic needs. This research was conducted through observation methods, interviews with the Head of Lefokisu Village and the community in Lefokisu Village to obtain a real picture of the contribution of the agricultural sector to the community's economic life. The results of the study indicate that agricultural commodities play a significant role in increasing community income. Based on interviews, the community explained that agricultural products such as corn processed into titi corn and tamarind and cashew seeds are commodities of economic value that help meet daily needs. Overall, agricultural commodities in Lefokisu Village have great potential and play a significant role in supporting the village economy, especially through the processing and utilization of local agricultural products managed directly by the community.